Peningkatan kompetensi pedagogik guru melalui pelatihan perangkat pembelajaran abad-21 berbasis merdeka belajar di Kabupaten Pelalawan Riau - Ahmal Ahmal; Supentri Supentri; Piki Setri Pernantah; Mirza Hardian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Improving the quality of education and teaching is a must and absolutely for all elements of education in this country, not except for a teacher. Good teachers are teachers who understand and understand their responsibilities and obligations. The teacher is the key actor in the learning. Teachers must follow learning trends that are relevant to current conditions, namely 21st century learning. To develop 21st century learning based on “merdeka belajar”, teachers must carry out student-center learning. The learning tools developed must have the principles of efficiency, effectiveness, and be learner-oriented. This is done by considering the readiness, interest and learning needs of students in the classroom so that they can achieve maximum learning goals and national education goals. This community service activity is implemented using a workshop method for 3 (three) days with speakers by lecturers according to their fields of expertise and in collaboration with the FOGIPSI organization. This event seeks to provide understanding, guidance, and experience for teachers in Pelalawan Regency related to 21st century learning tools based on “merdeka belajar” that are relevant to the current era of the industrial revolution 4.0.